2021
DOI: 10.1088/1755-1315/655/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management conceptual framework in Nigeria tertiary institutions

Abstract: Knowledge is an essential resource to academic institutions, but its management especially in the developing countries has always been very difficult. A KM model is developed in this study to manageinstitutional resources and makesame available at the right time towards enhancing academic performance. Quantitative research approach was adopted over content analysis to evaluate data obtained through the review of the past related works on KM models. The study framework is based on some established models and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Supporting the position above, Favoretto and Carvalho (2021) believe that any policy that encourages employees to release any information capable of solving the problems facing the organisation is termed knowledge management. In congruence with the above, Ogunbanwo et al (2021) argued that employees may possess accurate knowledge that can be used to tackle the organisational problem but the implementation is domiciled with the managers. What this implies is that an employee can have knowledge that would turn around the future of the business but sometimes managers may not give them that opportunity because of the fear of losing their position (Sayyadi 2009;Favoretto and Carvalho 2021).…”
Section: Knowledge Managementmentioning
confidence: 94%
See 1 more Smart Citation
“…Supporting the position above, Favoretto and Carvalho (2021) believe that any policy that encourages employees to release any information capable of solving the problems facing the organisation is termed knowledge management. In congruence with the above, Ogunbanwo et al (2021) argued that employees may possess accurate knowledge that can be used to tackle the organisational problem but the implementation is domiciled with the managers. What this implies is that an employee can have knowledge that would turn around the future of the business but sometimes managers may not give them that opportunity because of the fear of losing their position (Sayyadi 2009;Favoretto and Carvalho 2021).…”
Section: Knowledge Managementmentioning
confidence: 94%
“…Deviating from the above submission, Kassaneh et al (2021) and Perevozova et al (2019) suggested that knowledge management is not only domiciled with human resource professionals but it is a tool that can be used to attract new ideas or innovations from within or outside the organisation. Still, in the search for what knowledge management represents, Ogunbanwo et al (2021) argued that knowledge management refers to a process of acquiring new knowledge, keeping it in databases as storage, and utilizing it for the benefit of the organisation. Simplifying it further, Edeh et al (2022) contended that knowledge management is human resource nomenclature that is concerned with knowledge acquisition, knowledge storage, and knowledge sharing or distribution amongst coworkers to achieve formulated goals.…”
Section: Knowledge Managementmentioning
confidence: 99%
“…Five identified success factors are support from leadership, organization culture, processes and activities within the organization, use of technology and people. Ogunbanwo, Okesola, & Sheryl, (2021) stated that knowledge is an essential resource to academic institutions, but its management especially in the developing countries has always been very difficult. KM model is developed in this study to manage institutional resources and make same available at the right time towards enhancing academic performance.…”
Section: Introductionmentioning
confidence: 99%